Sleep disorders in acute and chronic pain - M. G. Poluektov (Nevrologiâ, Nejropsihiatriâ, Psihosomatika, 2021)
Pain is one of the leading causes of decline in quality of life. When pain syndromes occur, a person may experience unpleasant sensory sensations and concomitant disorders, which can lead to pain aggravation and sleep disturbances. According to experimental studies, increased pain sensation with reduced sleep duration occurs due to opioid, serotonergic, noradrenergic, and dopaminergic antinociceptive systems dysfunction. In clinical practice, a reduction in sleep duration is usually associated with insomnia, which is the most common sleep disorder. In pain syndromes, insomnia occurs in 53–90% of patients (for comparison: in the general population – in 7.4%). Non-pharmacological (cognitive-behavioral therapy) and pharmacological approaches are used in insomnia treatment. Some medications (amitriptyline, mirtazapine, trazodone, gabapentin, pregabalin) have both hypnotic and analgesic effects, which allows to use them for pain syndromes with sleep disturbances. It has been shown that the correction of sleep disorders can reduce the severity and frequency of pain.